DADPRO Marketing Communication Strategy In Attracting Corporate Cli-ents In Makassar: A Study Of Communication Management Based On SWOT Analysis - Andika Andika; Muh. Akbar; Muh. Iqbal Sultan; Sultan Sahrir (IHSA Institute, 2026)
Global digital developments encourage companies to implement a more integrated and adaptive marketing communication strategy to technological changes. The event organizer industry in Makassar faces increasingly fierce competition so that the right strategy is needed to attract corporate clients. This study aims to analyze DADPRO's marketing communication strategy in attracting corporate clients with a communication management approach based on SWOT analysis. This study uses a descriptive quantitative method with data collection techniques through questionnaires, observations, and documentation of 44 respondents selected using purposive sampling. Data analysis was carried out using IFAS and EFAS matrices to identify the company's internal and external factors. The results of the study showed that DADPRO had an IFAS value of 2.43 and an EFAS of 2.84 which placed the company in Quadrant I (aggressive strategy). This shows that DADPRO has great strength and opportunity in developing marketing communication strategies, especially through digital marketing and personal approaches. The conclusion of this study shows that DADPRO is in a strategic position to grow, but it needs to improve digital marketing integration, HR competence, and brand strengthening